Georges Lemoine dans le creuset Delpire - Christine Plu (Strenae)
This article examines how Georges Lemoine's time working at the Delpire-Advico advertising agency as a graphic designer shaped his career as an illustrator.It also sheds indirect light on Delpire's editorial practices, which influenced Lemoine's work, and can be seen particularly in areas cherished by both men: in the typography, the page layout, and the search for a modern aesthetic that was innovative yet spare.